2019
DOI: 10.1016/bs.mie.2019.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Design of RNA-targeting macrocyclic peptides

Abstract: RNA structures play a pivotal role in many biological processes and the progression of human disease, making them an attractive target for therapeutic development. Often RNA structures operate through the formation of complexes with RNA-binding proteins, however, much like protein-protein interactions, RNA-protein interactions span large surface areas and often lack traditional druggable properties, making it challenging to target them with small molecules. Peptides provide much greater surface areas and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Although the field of de novo designed proteins capable of binding to nucleic acids is relatively under researched, there have been advances that use other design methods which may offer engineering insights. Walker and Varani discuss their approach in designing peptides capable of binding to RNA, which focused mainly on structure based peptidomimetics [ 61 ]. These are designed peptides meant to mimic the sequence and structure of proteins known to interact with RNA.…”
Section: Design Of Dna/rna Binding Proteinsmentioning
confidence: 99%
“…Although the field of de novo designed proteins capable of binding to nucleic acids is relatively under researched, there have been advances that use other design methods which may offer engineering insights. Walker and Varani discuss their approach in designing peptides capable of binding to RNA, which focused mainly on structure based peptidomimetics [ 61 ]. These are designed peptides meant to mimic the sequence and structure of proteins known to interact with RNA.…”
Section: Design Of Dna/rna Binding Proteinsmentioning
confidence: 99%
“…Many RNA binding proteins recognize RNA molecules through arginine-rich motifs (ARMs), as they are relatively shorter in length, have little sequence similarity (aside from containing many arginine residues), and adopt diverse conformations (including an α-helix and a β-hairpin) upon association with the viral RNA. The experimental work using X-ray crystallography and nuclear magnetic resonance (NMR) methods on the peptide–RNA complexes has demonstrated that the RNA backbone interacts with peptides more commonly than the nucleotide bases, suggesting that the majority of peptide–RNA interactions are nonspecific. , Overall, these studies showed that the peptide–RNA interactions occur through dynamic rearrangements in both molecules, which often entail backbone shifts and the flipping of nucleobases and amino acid residues. , Moreover, recent studies have demonstrated that the β-hairpin peptides could be synthesized with ultrahigh affinity toward viral RNA molecules. However, a de novo design of α-helical peptides that potently and selectively recognize viral RNA molecules is limited due to a poor understanding of the RNA recognition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The peptide hydrogen bond (HB) is a crucial non-covalent interaction that is implicated in the stabilization of various secondary structures like β-turn 1, 2 , 3 10 -helix [3][4][5] , α-helix 6,7 , π-helix 8 , random loops 9,10 . These secondary structures play important roles in several biological recognition processes through protein-protein 11,12 , protein-DNA 13,14 , protein-RNA interactions 15,16 and as hormones 9, 10 , antibiotics 1, 2 , ion-channels 3,4,[17][18][19] and in signal transduction 20 , protein folding 21,22 . Recognitions tend to be prevalently along with peptide sequences between the hydrogen bond constraint 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Seal the separatory funnel again with polyethylene cap, shake the reaction mixture and settle down for 2 min until two layers are separated out. 16. separate the aqueous layer and pass the organic layer through the crystalline sodium sulphate to remove the residual amount of water and collect in 100 ml one neck RBF.…”
mentioning
confidence: 99%